Metabolic predictors of individual immune responses to adaptogenic balneotherapy - Zoryana Struk; Oksana Mel'nyk; Walery Zukow; Igor Popovych (Kazimierz Wielki University, 2020)
Background. Earlier four variants of the immune responses to adaptogenic balneotherapy have been identified. All four variants of immune responses are virtually unmistakably (with an accuracy of 97,7%) predicted by a set of 20 predictors including 12 immune blood parameters and one saliva parameter, 4 information parameters, 2 fecal microbiota parameters as well as erythrocyturia. In the next study discriminant analysis revealed that constellation 8 HRV and 5 Endocrine parameters as well as Gender of the patient predicts the nature of the immune response with an accuracy of 90,9%. The purpose of this study is to search for predictors of immune responses among the registered Metabolic parameters. Material and methods. Theobjectofobservationwere 34menand 10 womenaged24-70yearsold,whocametotheTruskavets' spa for the treatment of chronic pyelonephritis combined withcholecystitis inremission. We determined them theElectrokinetic index, Lipoproteines spectrum, plasma and daily urine levels of Electrolytes and Nitrous metabolites as well as basal and postprandial volume of gall-bladder. Results. Discriminant analysisrevealed 16 parameters as the predictors. Of these, 3 reflect the level of Plasma Electrolytes, 5 - the Urine Electrolytes, another 2 - the levels of plasma and urine Urea.